Peran Dewan Syariah Nasional – Majelis Ulama Indonesia (DSN-MUI) Dalam Penegakan Hukum Ekonomi Syariah Di Indonesia - Arif, Nik Muhammad; Rahardi, Mohamad Tedy (TERAJU: Jurnal Syariah dan Hukum, 2023)
The purpose of establishing the DSN-MUI is to realize and answer questions from Muslims in Indonesia regarding economic problems for which the exact laws in Islamic teachings are not yet known, as well as responding to issues related to economic/financial problems. The research method used in this research is qualitative. with the aim of describing, explaining, explaining and answering in detail the problems studied. Since its inception until now, DSN-MUI has had an important role in sharia financial institutions, such as Bank Indonesia Regulations (now POJK) which emphasize that all sharia banking products may only be offered to the public after the bank has received a fatwa from DSN-MUI and obtained permission from OJK.